The reproducibility of cardiopulmonary responses to exercise using a swim bench - Swaine, I. L.; Zanker, C. L. (International Journal of Sports Medicine, 1996)
The purpose of this study was to establish reproducible assessments of cardiopulmonary responses to exercise using a computer-interfaced isokinetic swim bench. Five male and four female highly trained swimmers with mean age of 19.2 +/- 1.2 (yrs), stature 1.75 +/- 0.02 (m) and body mass of 65.8 +/- 2.9 (kg) performed an incremental exercise test on two occasions within one week. Oxygen consumption (VO(2)), heart rate (HR) and exercise intensity were recorded throughout the exercise test. Measurements were made of the peak oxygen consumption (VO(2peak)), peak heart rate (HR(peak)) peak exercise intensity (EI(peak)) and the submaximal heart rate vs exercise intensity (HR/EI) and oxygen consumption vs exercise intensity (VO(2)/EI) relationships. The values for VO(2peak), HR(peak) and EI(peak) from all tests were 2.85 +/- 0.26 (I.min(-1)), 171 +/- 2.8 (b.min(-1)) and 86.2 +/- 6.8 (watts) respectively. The differences in these peak values from repeated tests were 0.06 I.min(-1), 1.8 b.min(-1) and 1.3 W, which were not significant (p > 0.05; paired t-test). These represented 2.1, 1.0 and 1.5% respectively. The HR/EI and VO(2)/EI relationships were shown to be linear (at least r = 0.99 and r = 0.98 respectively) and the differences in these relationships from repeated tests were not significant (p > 0.05, ANCOVA) showing adjusted mean differences of 0.02 I.min(-1) and 0.5 b.min(-1) for the group. These results suggest that this method, which uses a swim bench, provides reproducible measurement of the cardiopulmonary responses to exercise in swimmers.